THE EFFECT OF CALCINATION ON MICROWAVE ABSORBING PROPERTIES OF Fe3O4/TiO2 COMPOSITE - Adel Fisli; Didin Sahidin WinataPura; Wisnu Ari Adi; Yana Taryana (Jurnal Sains Materi Indonesia, 2019)
THE EFFECT OF CALCINATION  ON MICROWAVE ABSORBING PROPERTIES OF Fe3O4/TiO2 COMPOSITE. The Fe3O4/TiO2 composites have been fabricated by simple precipitation method for microwave absorbing. The obtained powder of Fe3O4/TiO2 which 10 % iron oxide containing were calcinated from 300oC – 700oC for 3 hours. The characteristic of samples was investigated by various techniques. The TEM image showed the composites form agglomeration with particles size of around 20 nm.  The all sample contents most of the anatase phase. The increasing of calcination temperature is the bigger of crystallite size. The Raman bands shift towards lower wavenumber and their full-widths at half-maximum (FWHM) of the bands decreases as the particles size increase. The measurement of the magnetic properties illustrated that the Fe3O4/TiO2 exhibited paramagnetic behavior at room temperature. The microwave absorbing properties of the sample was measured by VNA  using frequency microwave filter in  X-band range  (8-12 GHz). The reflection loss (RL) values were calculated for thickness 1 mm of the sample. The minimum reflectivity peak value tends to decrease with the increase of the calcination temperature due to increasing the crystallite size of the particles. The lowest reflectivity value of Fe3O4/TiO2 was occurred calcinated at 600oC with -13.4 dB loss at 10.9 GHz, that is more 80% absorbed of the electromagnetic wave in thickness 1 mm of the sample. The microwave absorption properties the calcinated 700oC the sample decrease due to the loss of magnetic properties of the sample. This study concluded that increase in average crystalline size, microwave absorption properties increased. However, the decrease dratisly of magnetic properties of the sample causes microwave absorption properties to decrease.